Favipiravir and Zanamivir Cleared Infection with Influenza B in a Severely Immunocompromised Child. (3rd March 2020) - Lumby, Casper K; Zhao, Lei; Oporto, Macarena; Best, Tim; Tutill, Helena; Shah, Divya; Veys, Paul; Williams, Rachel; Worth, Austen; Illingworth, Christopher J R; Breuer, Judy
Abstract: A combination of favipiravir and zanamivir successfully cleared influenza B infection in a child who had undergone bone marrow transplant for X-linked severe combined immunodeficiency, with no recovery of T lymphocytes. Deep sequencing of viral samples illuminated the within-host dynamics of infection, demonstrating the effectiveness of favipiravir in this case.